The psychometric properties of the Persian version of the posttrauma risky behaviors questionnaire in individuals with post-traumatic stress disorder symptoms - Ehsan Bedayat; Nurallah Mohammadi; Changiz Rahimi Taghanaki; Abdulaziz Aflakseir (مجله علوم روانشناختی)
Background: Despite the addition of a new diagnostic criterion indicating the degree of involvement in reckless or self-destructive behaviors for PTSD in the Diagnostic and Statistical Manual - Fifth Edition, research evidence indicates that a reliable and valid tool for assessing and diagnosing it has not been found to exist in Persian. Aims: The purpose of this study was to investigate the psychometric properties of the Persian version of the posttrauma risky behaviors questionnaire. Methods: The current research was an applied survey study based on a test construction methodology, following the common principles and techniques of psychometrics in a correlational research design. The statistical population for this research included all people with symptoms of post-traumatic stress disorder in 2023 living in shiraz. A total of 520 participants (365 female and 155 male) were selected using the International Trauma Questionnaire (Cloitre et al., 2018) through convenience sampling Methods: They then completed the Posttrauma Risky Behaviors Questionnaire (Contractor et al., 2020), the Self-Harm Inventory (Sanson et al., 1998), and the self-destructive behaviors questionnaire (Aghamohammadian Shearbaf et al., 2013). Data analysis was done using SPSS26 and AMOS26 software at a significance level of 0.05. Results: The confirmatory factorial analysis supported a one-factor model with desirable fit indices (X2/df= 3.239, GFI= 0.930, IFI= 0.924, CFI= 0.924, RMSEA= 0.066). Cronbach's alpha coefficient of the Posttrauma Risky Behaviors Questionnaire was 0.85. The self-destructive behaviors questionnaire (31 items; r= 0.01, p< 0.660) and the Self-Harm Inventory (22 items; r= 0.01, p< 0.532) showed a positive and significant correlation with the Posttrauma Risky Behaviors Questionnaire. Conclusion: Overall, the results of the present study provided evidence for the validity and reliability of the posttrauma risky behaviors questionnaire as a tool for comprehensive, brief, and one-dimensional assessment of reckless or self-destructive behaviors. Therefore, it can be used by researchers, therapists, and psychologists as a reliable and valid tool.